Broadband radiative properties of cirrus clouds deduced from aircraft measurements during fire - Smith, William L., Jr., author; Cox, Stephen K., author (Colorado State University. Libraries, 1989)
The bulk radiative and microphysical properties of five cirrus clouds sampled via the NCAR Sabreliner on four days during the FIRE first cirrus IFO are described. These cirrus systems, which developed under a variety of synoptic weather conditions, occurred at various altitudes and ranged in geometric thickness from about 2.0 to 4.5 km. A broadband, infrared radiative transfer model is employed to deduce the impact of the cirrus layers on infrared radiation. This model isolates the effect of the atmospheric gases from that of the cloud ice water permitting retrieval of the cloud emittance ( £c1d) and profiles of the mass absorption coefficient (K). For the five cirrus cloud cases, the total cloud emittance, £c1d, ranged from about 0.4 to 0.8 and the deduced emittance profiles appear as similar functions of ice water path (IWP) Furthermore, the mass absorption coefficient, K, is found to decrease with increasing particle size ranging from about 0.48 m2g-1 in the top of one layer to about 0.007 m2g-3 near the base of another. This relationship is somewhat dissimilar from one cirrus system to the next suggesting the significant effect of some unmeasured microphysical property. Small particles, which have been shown by other authors to be prevalent in cirrus clouds via the spectral characteristics remotely sensed in the 8-12 μm window region, are a likely suspect. Broadband, infrared absorption coefficients (u) are also computed and found to exhibit a similar temperature dependence as data recently presented by other authors. The horizontal variabilities in the shortwave and infrared properties of these cirrus systems are explored. The range of variation in the shortwave properties are found to be similar to the observed range in the infrared. Good correlation was found between the shortwave albedo (p) and upward effective emittance (c• i). A scatter plot of these two parameters agreed well with theoretical calculations assuming an asymmetry parameter of 0.7. Downward effective emittances (c• !) were found to range from about 0.4 to 0.8, while the shortwave effective extinction (~) ranged from 0 to 0.45. c• ! and were not well correlated owing to cloud heterogeneities. Finally, the current state of cirrus radiation parameterizations was briefly assessed in relation to this data set and there appears to be sufficient observational evidence to support the initial development of parameterization schemes for general circulation and climate models.
October 1989.
Also issued as William L. Smith's thesis (M.S.) -- Colorado State University, 1989.
Keywords: Atmospheric radiation; Cloud physics